Wetting, Superhydrophobicity, and Icephobicity in Biomimetic Composite Materials - (:unkn) unknown (My University, 2014)
Recent developments in nano- and bio-technology require new materials. Among these new classes of materials which have emerged in the recent years are biomimetic materials, which mimic structure and properties of materials found in living nature. There are a large number of biological objects including bacteria, animals and plants with properties of interest for engineers. Among these properties is the ability of the lotus leaf and other natural materials to repel water, which has inspired researchers to prepare similar surfaces. The Lotus effect involving roughness-induced superhydrophobicity is a way to design nonwetting, self-cleaning, omniphobic, icephobic, and antifouling surfaces. The range of actual and potential applications of superhydrophobic surfaces is diverse including optical, building and architecture, textiles, solar panels, lab-on-a-chip, microfluidic devices, and applications requiring antifouling from biological and organic contaminants. In this thesis, in chapter one, we introduce the general concepts and definitions regarding the wetting properties of the surfaces. In chapter two, we develop novel models and conduct experiments on wetting of composite materials. To design sustainable superhydrophobic metal matrix composite (MMC) surfaces, we suggest using hydrophobic reinforcement in the bulk of the material, rather than only at its surface. We experimentally study the wetting properties of graphite-reinforced Al- and Cu-based composites and conclude that the Cu-based MMCs have the potential to be used in the future for the applications where the wear-resistant superhydrophobicity is required. In chapter three, we introduce hydrophobic coating at the surface of concrete materials making them waterproof to prevent material failure, because concretes and ceramics cannot stop water from seeping through them and forming cracks. We create water-repellant concretes with CA close to 160o using superhydrophobic coating. In chapter four, experimental data are collected in terms of oleophobicity especially when underwater applications are of interest. We develop models for four-phase rough interface of underwater oleophobicity and develop a novel approach to predict the CA of organic liquid on the rough surfaces immersed in water. We investigate wetting transition on a patterned surface in underwater systems, using a phase field model. We demonstrated that roughening on an immersed solid surface can drive the transition from Wenzel to Cassie-Baxter state. This discovery improves our understanding of underwater systems and their surface interactions during the wetting phenomenon and can be applied for the development of underwater oil-repellent materials which are of interest for various applications in the water industry, and marine devices. In chapter five, we experimentally and theoretically investigate the icephobicity of composite materials. A novel comprehensive definition of icephobicity, broad enough to cover a variety of situations including low adhesion strength, delayed ice crystallization, and bouncing is determined. Wetting behavior and ice adhesion properties of various samples are theoretically and experimentally compared. We conclude superhydrophobic surfaces are not necessarily icephobic. The models are tested against the experimental data to verify the good agreement between them. The models can be used for the design of novel superhydrophobic, oleophobic, omniphobic and icephobic composite materials. Finally we conclude that creating surface micro/nanostructures using mechanical abrasion or chemical etching as well as applying low energy materials are the most simple, inexpensive, and durable techniques to create superhydrophobic, oleophobic, and icephobic materials.
Keywords: Biomimetic; Composites; Contact Angle Hysteresis; Icephobicity; Oleophobicity; Superhydrophobicity